The advantage of transparent instruments of monetary policy - Atkeson, Andrew 1961-; Kehoe, Patrick J. (NBER working paper series, 2001)
Is the exchange rate or the money growth rate the better instrument of monetary policy? A common argument is that the exchange rate has a natural advantage because it is more transparent: it is easier for the public to monitor than the money growth rate. We formalize this argument in a simple model in which the government chooses which instrument it will use to target inflation. We find that when the government cannot commit to its policies, the greater transparency of the exchange rate makes it easier to provide the government with incentives to pursue good policies. Hence, transparency gives the exchange rate a natural advantage over the money growth rate as the monetary policy instrument.